From function to wellbeing: healing design strategies in contemporary outdoor fashion - Li, Yijing; Kam, Seonju (Frontiers in Psychology, 2025)
IntroductionThis study explores outdoor fashion as a medium for promoting psychological wellbeing, functional comfort, and sociocultural connection. As leisure, health, and identity converge, the research conceptualizes the components of healing environments, defines key healing design characteristics, and analyses their practical applications in outdoor fashion to support psychosocially responsive design strategies.MethodsA literature review established theoretical links between four types of healing environments (physical, functional, social, and psychological) and eight healing design characteristics (pleasantness, independence, accessibility, openness, safety, aesthetic quality, biophilic quality, and sociality). A case analysis of 805 products from six global outdoor brands (2021–2024) examined structural, pattern, material, and color elements. Coding reliability was verified through expert validation and Cohen’s Kappa analysis (κ = 0.74–0.76).ResultsOutdoor fashion integrating healing design principles combined structural, pattern, material, and color elements that theoretically support psychological, physical, and social wellbeing. Ergonomic, semi-open, and adjustable structures enhanced comfort, independence, and safety; nature-inspired and geometric patterns strengthened biophilic connection and cultural identity; soft and reflective materials provided tactile comfort and perceived security; and color strategies influenced emotional stability, visibility, and aesthetic quality. Comfort, aesthetic quality, and psychological stability emerged as shared brand priorities, and the integrated use of multiple elements generated stronger healing effects than isolated features.DiscussionFindings indicate that outdoor fashion serves as a transdisciplinary platform that integrates psychological, functional, and sociocultural dimensions of care. Theoretical associations suggest that holistic combinations of design elements can enhance wellbeing by addressing sensory, emotional, and physical needs simultaneously. The proposed framework provides practical guidance for health-oriented design across commercial, community, and therapeutic contexts. However, these interpretations are theoretical rather than causal, and empirical user-based studies are required to validate the psychological and physiological associations identified.